2021
DOI: 10.1088/1755-1315/934/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Domestication Strategies of Tinfoil Barb Barbonymus schwanenfeldii (Bleeker, 1854): Potential Candidate for Freshwater Aquaculture Development

Abstract: This paper discussed domestication strategies of Tinfoil barb from different populations for evaluation of potential fish candidate for freshwater aquaculture development. Collection and maintenance of wild-caught adult fish was the first step in domestication strategies followed by characterization of fish, broodstocks selection and maturation, control of fish reproduction, and larval rearing. The Tinfoil barb presented an excellent performance to adapt to the new environment. This was indicated by survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the cleavage phase, the embryo of Torfish species lasts for 10 hours. Furthermore, the process of embryo development in Oryzias woworae species occurs for 1 hour 20 minutes 9 . While the results of observations on the cleavage phase of the embryo in Tawes fish lasted for 2 hours 24 minutes after fertilization (Naskuroh et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In the cleavage phase, the embryo of Torfish species lasts for 10 hours. Furthermore, the process of embryo development in Oryzias woworae species occurs for 1 hour 20 minutes 9 . While the results of observations on the cleavage phase of the embryo in Tawes fish lasted for 2 hours 24 minutes after fertilization (Naskuroh et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In Indonesia, the domestication of TB began with characterizing the genotype, morphological, and biological reproduction of 3 populations, Sumatra, Java, and Kalimantan (Kusmini et al, 2018;Radona et al, 2016a,b), followed by a series of performance evaluations to have the best populations for the domestication program (Radona et al, 2016a,b;Radona et al, 2018;Kusmini et al, 2021). After several generations, investigations of breeding performance showed populations from Kalimantan had the highest growth performance compared to other populations for specific growth rates, survival rates, and feed conversion ratios (Kusmini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At a later stage, domestication testing was carried out to evaluate the performance of the Kalimantan population generation obtained to determine the domestication strategy to be carried out (Kurniawan et al, 2021). In the progress of domestication of TB, the promising candidate showed that the mature broodstock was indicated in the weight of 150 to 400 g for females and 200 to 400 g for males (Kusmini et al, 2021), within the size range of the adult wild Barbonymous species (Efizono et al, 2021). The broodstocks reached their gonad maturity level by spawning twice a year.…”
Section: Introductionmentioning
confidence: 99%